Failure mechanisms and dynamic process control measures of deep buried tunnels in tectonic fracture zones under high in-situ stresses—a case study in Southwestern China - Zheng, Keyue; Shi, Chenghua; Zhao, Qianjin; Lei, Mingfeng; Jia, Chaojun; Lou, Yili (Frontiers in Earth Science, 2023)
Squeezing deformation in tectonic fracture zones under high in-situ stresses has created great difficulties to deep tunnel construction in Southwestern China. This study reports an investigation on large deformation and failure mechanisms of the Wanhe tunnel on the China-Laos Railway through several field tests including the in-situ stress, loosened zone, deformation monitoring, and internal stresses of steel arches. The dynamic process control method is proposed following the combination principle of stress releasing and support resistance. Further, the dynamic process control measures including the advanced and primary supports, the deep-shallow coupled delayed grouting method, and the double steel arches method were applied on site to resist the deformation development. The results of this study indicate that the rapid growth of the tunnel deformation in the early stage was caused by the squeezing effect, and later the loosening effect led to another growing trend of the vault settlement. The dynamic process control method allows to release the deformation of the surrounding rock in the rapid growth stage. Then, it requires to control the deformation within the reserved range by reinforcing the surrounding rock and increasing the stiffness of supports in the later stage. From the feedback of monitoring results, large deformation of Wanhe tunnel was well released and effectively controlled within the deformation allowance. Thus these countermeasures based on the dynamic process control method can guarantee the construction safety of deep buried tunnels in tectonic fracture zones under high in-situ stresses.